Atomic-scale control of friction by actuation of nanometer-sized contacts - Socoliuc, Anisoara; Gnecco, Enrico; Maier, Sabine; Pfeiffer, Oliver; Baratoff, Alexis; Bennewitz, Roland; Meyer, Ernst (Science, 2006)
Stiction and wear are demanding problems in nanoelectromechanical devices, because of their large surface-to-volume ratios and the inapplicability of traditional liquid lubricants. An efficient way to switch friction on and off at the atomic scale is achieved by exciting the mechanical resonances of the sliding system perpendicular to the contact plane. The resulting variations of the interaction energy reduce friction below 10 piconewtons in a finite range of excitation and load, without any noticeable wear. Without actuation, atomic stick-slip motion, which leads to dissipation, is observed in the same range. Even if the normal oscillations require energy to actuate, our technique represents a valuable way to minimize energy dissipation in nanocontacts.